Development and Characterization of Gelatin Films Enriched With Olive Leaves Extract for Fresh Apple Packaging - Kareem, Israa Hawyyiz; Mohammed, Azheen Othman (American Journal of Biodiversity, 2025)
To minimize microbial growth, food preservation must employ a variety of physical and chemical techniques. As an alternative to traditional synthetic materials that can be harmful to the consumer’s health, the packaging materials could be derived from biological sources, such plants. The study was aimed to development and characterization of gelatin films enriched with olive leaves extract for fresh Apple packaging. In October 2024, olive leaves were gathered from olive trees in Kirkuk, Iraq. After being gathered, the leaves were cleaned with tap water and allowed to dry for 30 days at room temperature (between 25 and 30 °C). Distilled water was used to dissolve the gelatin powder at 60 °C and a 3% (w/v) concentration. The leftover extracts from olive leaves were then dissolved at 5, 10, and 20 µg/ml in the gelatin film-forming solution. The findings showed that the highest percentage of thickness was in the 8% olive leaves treatment in the first week of apple storage (0.21±0.04), and even after the fourth week of treatment and for the 8% olive leaves film (0.18±0.04) compared to the control treatment and the rest of the treatments. gelatin films containing olive leaves had tensile strengths ranging from 55.52±3.89 in T1 at the first week to 23.11±5.12 in T3 at the fourth week MPa. In terms of elongation rate, it was 5.37±0.31 in T3 during the first week in the extract-supported film, which was more than the elongation rate of control treatment 4.21±0.09. In every week and transaction, it outperformed the control group. the edible film made with gelatin without olive leaves has a significantly (P<0.05) different WVT than the edible film made with olive leaves at varying concentrations. It appears that the highest percentage of WVT was in the control treatment in the first week of apple storage (0.08±0.005), and even after the fourth week of treatment, 8% olive leaves film (0.05±0.003) less than control treatment and the rest of the treatments. It is concluded that adding olive leaves extract to gelatin Edible Films led to enhancing the chemical and mechanical properties of the edible film.